TEACHING GENDER AWARENESS THROUGH FAIRY TALES IN THE EFL CLASSROOM - Arisa Kochiyama (English Review: Journal of English Education, 2013)
Abstract: The purpose of this study is to explore how gender has been portrayed historically and in current times in fairy tales and then to introduce the effectiveness of using fairy tales in language instruction. While some instructors may still believe that teaching EFL encompasses focusing on linguistic elements only, recent trend in EFL teaching indicates the necessity of integrating literature in the curricula because of its rich potential to provide an authentic model of language use as well as its universal themes within human history. Traditional fairy tales and modern ones can allow students to think critically about how men and women are portrayed and to compare these portrayals with their own communities. It is hoped that discussion of the topic of gender issues can help students foster critical thinking and literacy and empower them with a further understanding of gender notions in their lives.Keywords: intercultural communication, English as a second language, EFL classroom